Ta`ṡīr Istikhdāmi Lu’bah Al-Lughowiyyah “ Hal Ta’rifu As-Sabāb” ‘Alā Mahārati Al-Kalām bil Madrasati Ulun Nuhā - Nimas Amelia; Zulham Effendi; Ade Muhammad Ritonga (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2023)
Speaking skill is one of the most important skills in learning Arabic, and it is a form of language activity. It has been known in one of the schools, the students have problems speaking Arabic. from here, the author wants to make students have an interest and enthusiasm in speaking Arabic with the correct rules by using language games. The formulation of the problem in this study is whether there is an effect of using language games, “do you know why?” for learning to speak at Ulun Nuha School. and the purpose of this research is to find out the effect of the game “do you know why?” on learning to speak at Ulun Nuha school. The research is a quantitative method designed only control design for the true experimental post-test only design. Techniques of analysing research data using quantitative data with the product moment formula and test-t formula. And the results of this study using the t-test formula is to 2.259 greater than tt which is 2.003. The reciprocal hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected. Conclusion is that there is an effect of using the game